2018
DOI: 10.22201/fca.24488410e.2018.1653
|View full text |Cite
|
Sign up to set email alerts
|

Board compensation and disclosure quality: corporate governance interference

Abstract: This paper investigates the impact of financial information disclosure quality on board compensation in various corporate governance mechanisms in Iran. A unique data set from a sample of 176 Iranian listed firms over the period 2010-2016 is used in order to address the following questions: as an incentive mechanism for managers, is there any relationship between compensation and disclosure quality of financial information while some corporate governance factors are interfered? Duality on board, educated membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 134 publications
0
6
0
Order By: Relevance
“…In a recent scholarly investigation by Salehi and Farzaneh (2018), noteworthy findings have emerged, highlighting a positive correlation between a board's human capital and its performance, alongside the relationship between managerial share ownership and performance within the context of the Tehran Stock Exchange. Furthermore, the research conducted by Salehi et al (2018) reveals a significant and positive association between board compensation and disclosure quality, particularly in companies engaged in complex activities and foreign sales.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 97%
“…In a recent scholarly investigation by Salehi and Farzaneh (2018), noteworthy findings have emerged, highlighting a positive correlation between a board's human capital and its performance, alongside the relationship between managerial share ownership and performance within the context of the Tehran Stock Exchange. Furthermore, the research conducted by Salehi et al (2018) reveals a significant and positive association between board compensation and disclosure quality, particularly in companies engaged in complex activities and foreign sales.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 97%
“…Many studies that looked at board of director size discovered that a small board of directors is better than a large board of directors, arguing that more board members increase constraints to directors' communication and coordination and reduce board members' ability to supervise top management, resulting in more agency issues and a negative effect on company performance (Liang et al, 2013;O'Connell and Cramer, 2010). The presence of independent directors on the board is thought to reduce the usage of RPTs (Bona-S anchez et al, 2017; Salehi et al, 2018;Gavana et al, 2022;Ismail et al, 2022;Salehi et al, 2022a, b). Perry (2000), in his results, found that the director's bonus compensation has a positive effect on the director's performance.…”
Section: Board Of Directors' Characteristics and Rptsmentioning
confidence: 99%
“…The presence of independent directors on the board is thought to reduce the usage of RPTs (Bona-Sánchez et al. , 2017; Salehi et al. , 2018; Gavana et al.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Directors on corporate boards may receive equity-based compensation for their service. Sengupta and Zhang (2015) and Salehi et al (2018) set forth that such compensation offers private benefit incentives. The growth of directors' equity may direct board members to maximise the value of their own equity stake in the firm rather than safeguarding shareholder interests.…”
Section: Board Compensation and Disclosure Quality: Interference In C...mentioning
confidence: 99%